2011
DOI: 10.1161/atvbaha.111.235721
|View full text |Cite
|
Sign up to set email alerts
|

CCL20 Is Increased in Hypercholesterolemic Subjects and Is Upregulated By LDL in Vascular Smooth Muscle Cells

Abstract: Objective-Our aim was to analyze the regulation of CC Chemokine ligand 20 (CCL20) by LDL in human vascular smooth muscle cells (VSMC). Methods and Results-In asymptomatic subjects, circulating CCL20 levels were higher in patients with hypercholesterolemia (18.5Ϯ3.2 versus 9.1Ϯ1.3 pg/mL; PϽ0.01). LDL induced the expression of CCL20 in VSMC in a dose-and time-dependent manner. Increased levels of CCL20 secreted by LDL-treated VSMC significantly induced human lymphocyte migration, an effect reduced by CCL20 silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 52 publications
(49 reference statements)
3
41
0
1
Order By: Relevance
“…We demonstrate here, that inhibitors of NF-κB activation (BAY11-7082) and MAPK signaling (PD98059) were able to significantly decrease CCL20/CCR6 expression levels in mtBALB cybrids suggesting that expression of CCL20/CCR6 can be partially regulated by inhibition of NF-κB and/or MAPK signaling. This is in correlation with Calvayrac et al (39) and with Wang et al (40) who prevented the up-regulation of CCL20 by inhibiting of NF-κB. Additionally, it was indicated that NF-κB is involved in modulation of CCL20 by other mediators such as TNFα in some human cancer cells (41), prolactin in keratinocytes (42) or hypoxia in primary human monocytes (43).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We demonstrate here, that inhibitors of NF-κB activation (BAY11-7082) and MAPK signaling (PD98059) were able to significantly decrease CCL20/CCR6 expression levels in mtBALB cybrids suggesting that expression of CCL20/CCR6 can be partially regulated by inhibition of NF-κB and/or MAPK signaling. This is in correlation with Calvayrac et al (39) and with Wang et al (40) who prevented the up-regulation of CCL20 by inhibiting of NF-κB. Additionally, it was indicated that NF-κB is involved in modulation of CCL20 by other mediators such as TNFα in some human cancer cells (41), prolactin in keratinocytes (42) or hypoxia in primary human monocytes (43).…”
Section: Discussionsupporting
confidence: 77%
“…Fleming et al also demonstrated that chemokine CCL20 can enhance migratory capabilities of cutaneous keratinocytes (37) through up-regulating of CCL20 by inflammation (38). Moreover, Calvayrac et al (39) showed that increased release of CCL20 significantly induced human lymphocyte migration in transwell assay. Thus, we assumed that increased migration of mtBALB cybrids might be caused by higher expression of CCL20 in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies of NF-B inhibition in SMCs revealed that NF-B plays an important role in mediating IL-1␤-dependent induction of several of these genes. Although previous studies have demonstrated that NF-B mediates induction of several proinflammatory genes in SMCs including VCAM-1 and CCL20 (9,32), our unbiased analysis of transcription factor binding sites combined with NF-B inhibition studies in cultured SMCs provides novel evidence that NF-B is a major regulator of the marked and distinct inflammatory gene expression by IL-1. In addition, results reported here demonstrate novel roles for NF-B in promoting expression of proinflammatory genes such as P-selectin in SMCs.…”
Section: Discussionmentioning
confidence: 82%
“…Both CCR6 and its sole chemokine ligand CCL20 (also known as M acrophage I nflammatory P rotein [MIP] 3 α) are expressed at increased levels in human atherosclerotic plaques, and the circulating level of CCL20 is significantly increased in hypercholesterolemic subjects (Calvayrac et al 2011; Yilmaz et al 2007). In mice, Ccr6 and Ccl20 are both present constitutively in healthy aortas and in atherosclerotic plaques, and Ccr6 deletion in ApoE −/− mice fed a Western diet significantly reduced the atherosclerotic lesion size in both the whole aorta and the aortic root, accompanied by a reduction of macrophage content in the plaques (Wan et al 2011a).…”
Section: The Chemokine System As An Immunoregulator In Atherogenesismentioning
confidence: 99%